Krüppel-like factor 4 mediates cellular migration and invasion by altering RhoA activity. (1st January 2018) - Brauer, Philip R.; Kim, Jee Hun; Ochoa, Humberto J.; Stratton, Elizabeth R.; Black, Kathryn M.; Rosencrans, William; Stacey, Eliza; Hagos, Engda G.
Abstract: Kru¨ppel like factor 4 (KLF4) is a transcription factor that regulates genes related to differentiation and proliferation. KLF4 also plays a role in metastasis via epithelial to mesenchymal transition. Here, we investigate the function of Klf4 in migration and invasion using mouse embryonic fibroblasts and the RKO human colon cancer cell line. Compared to wild-type, cells lacking Klf4 exhibited increased migration-associated phenotypes. In addition, overexpression of Klf4 in Klf4 −/− MEFs attenuated the presence of stress fibers to wild-type levels. An invasion assay suggested that lack of Klf4 resulted in increased invasive capacity. Finally, analysis of RhoA showed elevated RhoA activity in both RKO and MEF cells. Taken together, our results strongly support the novel role of KLF4 in a post-translational regulatory mechanism where KLF4 indirectly modulates the actin cytoskeleton morphology via activity of RhoA in order to inhibit cellular migration and invasion.